Evaluation of air quality assessment in Seberang Jaya, Penang during Movement Control Order (MCO) 1.0 / Mohamed Syazwan Osman ... [et al.] - Osman, Mohamed Syazwan; Tengku Zahidi, Tengku Shamim Amelin; Khairudin, Khairunnisa; Nizam, Muhammad Ikhwan; ul-Saufie, Ahmad Zia (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Due to the recent global threat of COVID-19, World Health Organization (WHO) announced a Public Health Emergency of International Concern (PHEIC). The Malaysian government has taken several measures to combat the outbreak, with the goal of finally ceasing it. One of the major initiatives taken by the government was the implementation of the Movement Control Order (MCO). The Malaysian government's enforcement of MCO, which was intended to control the COVID-19 transmission throughout the country was believed to have an impact on the quantity of air pollutants emitted [1]. Several rules were implemented under MCO that greatly limited individuals' activities outside of their homes, such as only permitting critical industries to operate and suspending non-essential ones, which significantly decreased traffic density and the emission of industrial pollutants [2]. This study involved obtaining databases from the Department of Environment Malaysia (DOE), which were then utilised to perform various statistical analyses in OpenAir software to observe the quality of air pollutants emitted across the Seberang Jaya, Penang area. Simultaneously, a statistical analysis was employed using an R-package open-source software to analyse pollutants that were related to meteorological conditions. The main goal of this study was to analyse the overall quality of major air pollutants such as PM10, PM2.5, CO, NO2, SO2, and O3 during MCO 1.0 which began on the 18th of March 2020 to the 31st of May 2020. The data on wind direction and speed from DOE were critical to accomplish this study. In summary, the main pollutants emitted in Seberang Jaya were PM10 and PM2.5, and the locations where the greatest concentration of all pollutants detected were business areas. In the end, this study provided statistical analysis using the OpenAir software tool able to analyse the amounts of various types of air contaminants in this densely populated area of Seberang Jaya.